EPR studies of Mn-doped YBa₂Cu₃0₇-δ composites - Stepanov, A.A.; Gaillard, В.; Regnier, S.; Marfaing, J. (Физика низких температур, 1995)
The preliminary results of EPR experiments on superconducting Mn-YBaCuO composites are reported. The measurements were done in X band in the temperature range 4-300 K. Three distinct EPR components were observed possessing different g-factors and a rather different temperature behavior. For similar nonsuperconducting samples, only two signals were observed. The nature of the different components is discussed from the comparison of the results. It is shown that, among the superconducting samples, two of them originate from Mn²⁺ paramagnetic centers while the third one presumably comes from Cu²⁺ paramagnetic center. For the nonsuperconducting samples, a magnetic phase transition in an ordered state has been revealed at 25 K. This transition seems to be stimulated by the presence of Mn ions or clusters, probably located in the CuO chains.